Influence of crystal habit on the dissolution of simvastatin single crystals - Polona Bukovec; Anton Meden; Matej Smrkolj; Franc Vrečer (Acta Chimica Slovenica, 2015)
In order to achieve better in-vivo performance of the final dosage form comprising a poorly soluble drug the physicochemical properties of the active pharmaceutical ingredient can be altered not only by changing the solid state form but also through the conversion of their crystal habits. To elucidate this approach in the case of simvastatin, the dissolution behaviour of large crystals with the same internal structure but expressing different crystal habits was studied using atomic force microscope. The obtained differences in the dissolution were explained through the determination of crystal morphology its orientation and assignation of the molecular functional groups that were emerging on the surface of the dissolving crystal face. The dissolution rates of the particular crystal faces were found to be distinctly higher than others. The dissolution rate of single crystals differed as a consequence of higher incidence of more polar faces in case of rod shaped crystals isolated from more hydrophilic solvent mixture which we have established through a thorough research of the single crystal morphology, orientation and the assignation of specific functional groups for each of evolved crystal faces.